The impact of financial ratio to firm's financial distress / Nur Adlina Jamil - Jamil, Nur Adlina (2018)
This study has a motive which is to confirm whether the financial ratio was applicable to identify the impact for the firm's financial distress by using the logistic regression as a model in a way to predict the corporate failures in Malaysia over a three years period covering the 20 companies which consists of 17 companies from the Main Market and 3 companies from the Ace Market that listed on Malaysian Stock Exchange. There are 14 financial ratios was chosen that is the most often used from the past studies comes from 5 ratios of profitability ratios, 7 ratios of liquidity ratios, and 2 ratios of leverage ratios. This paper also determines whether all the PN 17 and GN3 companies that are listed on Bursa Malaysia website are actually facing financial failure. The secondary data were used and these are obtained through the review of literature which include the journal and published financial report. Besides that, the E-Views software was used to carry out the statistical analysis. This study chooses the terms of the ratios based on the previous studies. Thus, this study shows that even with more advanced statistical tools is more popularly used recently like the logistic regression analysis can be effective and reliable. Furthermore. the study was conducted using the recent data on the public listed companies in Bursa Malaysia. Therefore. this model is relevant in identifying the impact of financial ratio to firm's financial distress.